ESTUDO DA INTERAÇÃO DA CICLODEXTRINA COM FÁRMACOS VIA SIMULAÇÃO DE PRIMEIROS PRINCÍPIOS - Figueiredo, Jaciéli Evangelho de (2010)
Cyclodextrins, macrocyclic polymers, built up of units of D-()-α-glucopyranose (1-4). Have toroidal shape of truncated cone with a hydrophobic cavity in the form of donut in which various types of drugs may be included to form inclusion complexes. The cyclodextrin are three different types of structures that occur by enzymatic modification of six, seven or eight glucose units, called, respectively, α, β and γ-cyclodextrin. Recent studies show the possibility of using these substances in various biomedical applications as vehicles for delivering drugs and biological agents, and its goal of targeting drugs to carry the desired amount for the target and releasing it at a controlled rate. Additionally, by including the compounds can be protected against oxidation, degradation by light, heat losses and volatility, in addition, can prevent unpleasant tastes or odors. Considering possible biological applications of these compounds, this study aims to evaluate, through computer simulations based on first-principles Density Functional Theory (DFT), the interaction of α and β - cyclodextrin with drugs: aspirin, nimesulide and vitamin E. We will show that the α and β - cyclodextrins can include these compounds maintain their structures unchanged, with binding energies between -1.17 and -0.06 eV. Analyzing the structural and electronic properties, we can see what settings are most conducive to the carrying of drugs and thereby further demonstrated the potential of cyclodextrins for pharmaceutical and related applications.